2006
DOI: 10.1080/02698590600641024
|View full text |Cite
|
Sign up to set email alerts
|

Models of Machines and Models of Phenomena

Abstract: Experimental engineering models have been used both to model general phenomena, such as the onset of turbulence in fluid flow, and to predict the performance of machines of particular size and configuration in particular contexts. Various sorts of knowledge are involved in the method-logical consistency, general scientific principles, laws of specific sciences, and experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…[41] in which the author shows how new areas of application and investigative research have been found. The topic is further developed in other articles [42][43][44].…”
Section: Short Historical Reviewmentioning
confidence: 99%
“…[41] in which the author shows how new areas of application and investigative research have been found. The topic is further developed in other articles [42][43][44].…”
Section: Short Historical Reviewmentioning
confidence: 99%
“…Rather than trying to get hold on similarity between phenomena (Sterrett 2006), I thus focus on the similarity between derivations of phenomena. This brings me back to Kuhn's problem, that is, how do we know on which exemplar a new phenomenon can be modelled (Kuhn 1970, 190)?…”
Section: Derivational Redundancy and Derivational Similaritymentioning
confidence: 99%
“…Usually, this validation process is fragmented by the point of view of the researcher, the available techniques/materials, the knowledge accumulated etc. . Although it is widely accepted that a theory is usually criticized by falsification, mathematical models are often tested by validation; thus, a set of validations checks for all the main results should be undeniably performed …”
Section: Introductionmentioning
confidence: 99%
“…etc.. 1,2 Although it is widely accepted that a theory is usually criticized by falsification, mathematical models are often tested by validation; thus, a set of validations checks for all the main results should be undeniably performed. 3 The study of physical phenomena is mainly based on the concept of physical similarity.…”
mentioning
confidence: 99%